An analysis of pacing profiles of world-class racewalkers - Hanley, B. (International Journal of Sports Physiology and Performance, 2013)
Purpose: The aim of this study was to describe the pacing profiles used by racewalkers competing in IAAF World Championships. Methods: The times for each 5-km segment were obtained for 225 men competing over 20 km, 214 women competing over 20 km, and 232 men competing over 50 km, of whom 49 did not finish. Athletes were grouped based on finishing position (for medalists) or finishing time. Results: Different pacing profiles were used by athletes grouped by finishing time, with 20-km medalists using negative pacing and those finishing within 5% of the winning time matching the medalists` early pace but failing to maintain it. Lower-placed 20-km athletes tended to start more quickly relative to personal-best pace and experienced significant decreases in pace later. Across all competitions, the fastest finishers started the slowest relative to previous best performance. All 50-km athletes slowed toward the finish, but lower-placed finishers tended to decrease pace earlier (with up to 60% of the race remaining). After halfway in the 50-km, 8 of the 15 athletes who had a 5-km split more than 15% slower than the previous split dropped out. Conclusions: The negative pacing profile used by 20-km medalists required the ability to start fast and maintain this pace, and similarly paced training may be beneficial in race preparation. Over 50 km, the tactic of starting slower than personal-best pace was generally less risky; nonetheless, any chosen pacing strategy should be based on individual strengths.